Donald Davidson - Joseph, Marc, 1962- (Philosophy now., 2004)
Donald Davidson's work is of seminal importance in the development of the analytic tradition following Quine. His views on the nature of language, mind, and action occupy a prominent position in the philosophical literature and are a starting point for much of contemporary analytic philosophy. Davidson's article "Truth and Meaning" helped shape the debate over the proper approach to the semantics of natural language, just as "Actions, Reasons, and Causes" redirected discussions in action theory. His essay "Mental Events" partially defines contemporary discussion in its field, presenting one of the live options in the philosophy of psychology. His views are, however, extremely complex, interconnecting with one another in a myriad of ways and reinforcing one another in a way that makes it very difficult for students to understand his thinking by reading one or two of his articles. In this introduction to Davidson's philosophy Marc Joseph pulls together and examines Davidson's writings, illuminating the challenge of his critique and showing how it departs from the analytic tradition in novel and exciting ways.